2021
DOI: 10.1042/bcj20210626
|View full text |Cite
|
Sign up to set email alerts
|

Computational and in vitro experimental analyses of the Anti-COVID-19 potential of Mortaparib and MortaparibPlus

Abstract: COVID-19 pandemic caused by SARS-CoV-2 virus has become a global health emergency. Although new vaccines have been generated and being implicated, discovery and application of novel preventive and control measures are warranted. We aimed to identify compound/s that may possess the potential to either block the entry of virus to host cells or attenuate its replication upon infection. Using host cell surface receptor expression (Angiotensin-converting enzyme 2 (ACE2) and Transmembrane protease serine 2 (TMPRSS2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…229 In addition, Kumar et al found that, similar to N3 inhibitor, withanone could interact with the highly conserved residues of the proteases of coronaviruses, suggesting that withanone might be developed for the treatment of COVID-19. 230 Through molecular dynamics simulation analysis, withanolide R and 2,3-dihydrowithaferin A were also reported to bind to the main protease and the spike proteins of SARS-CoV-2, respectively, with the lowest relative free energy. 231 All these compounds need in vitro and in vivo experiments to confirm their effects on SARS-CoV-2 and evaluate their potential therapeutic effects on COVID-19.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…229 In addition, Kumar et al found that, similar to N3 inhibitor, withanone could interact with the highly conserved residues of the proteases of coronaviruses, suggesting that withanone might be developed for the treatment of COVID-19. 230 Through molecular dynamics simulation analysis, withanolide R and 2,3-dihydrowithaferin A were also reported to bind to the main protease and the spike proteins of SARS-CoV-2, respectively, with the lowest relative free energy. 231 All these compounds need in vitro and in vivo experiments to confirm their effects on SARS-CoV-2 and evaluate their potential therapeutic effects on COVID-19.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…However, the efficacy of none of these treatment options was found to be optimal against COVID-19, let alone the severe side effects, especially for immunocompromised cancer and diabetic patients (Di Lorenzo et al, 2020). During the initial phase of the pandemic, several in silico studies reported potentially effective metabolites against SARS-CoV-2 infection (Balkrishna et al, 2021a;Balkrishna et al, 2021b;Kumar V. et al, 2021;. Several herbal plants target immune responses by reducing cytokine levels (Li S. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The two antimicrobial peptides (ACAP-IV and ACAP-V) were docked against their respective target proteins. The molecular docking technique permits simultaneous investigation of thousands of molecules and later incorporates the ligand-target interactions to rank such molecules based on their binding affinities (Lionta et al, 2014;Kumar et al, 2020). The technique utilizes machine learning search algorithms to predict ligand-target binding sites and affinity (Shukla et al, 2020) and has been widely used to aid the discovery of several drugs including Captopril, Dorzolamide, Saquinavir, Zanamivir, Oseltamivir, Aliskiren, Boceprevir, Nolatrexed, TMI-005, LY-517717, Rupintrivir and NVP-AUY922 (Talele et al, 2010).…”
Section: Discussionmentioning
confidence: 99%